Assemi to be honored at Top Dog Gala as distinguished alumnus - Uribes, Tom::::::::: (2013)
Fresno entrepreneur and philanthropist Darius Assemi, president of Granville Homes, will be honored with the Fresno State Alumni Association's Top Dog Distinguished Alumnus Award for 2013 during the Top Dog Alumni Awards Gala.